Validation of the Signs of Inflammation in Children that can Kill (SICK) score for assessment of illness severity - Jose M. Mandei; Ari L. Runtunuwu; Chandni Daryanani (Paediatrica Indonesiana, 2013)
Background The Signs of Inflammation in Children that can Kill(SICK) score has been developed in the search for a practicaltriage tool in settings with limited resources for immediate, noninvasiveassessment of illness severity. Its seven parameters areheart rate, respiratory rate, systolic blood pressure, temperature,blood oxygen saturation (Sp02), capillary refill time (CRT), andlevel of consciousness. The SICK score also takes into accountthe age of the child.Objective To assess the validity of SICK scores for differentiatingbetween high and low probabilities of death in children.Methods We performed a prospective evaluation of all childrenaged between one month to twelve years admitted to the PediatricEmergency Care Unit at Prof. Dr. R.D. Kandou Hospital, Manadobetween October 2011 to January 2012. We calculated SICKscores at the time of presentation and assessed their correlationwith subsequent in-hospital mortality using logis tic regressionanalysis.Results During the study period, we observed 230 patients,of whom 199 survived and 31 died. There were 134 males, ofwhom 117 survived and 17 died. The remaining 96 subjects werefemale, of whom 82 survived and 14 died. Logistic regressionanalysis revealed a significant relationship between SICK scoreand mortality (P< 0.001). With a probability of 0.5, we attaineda cut off score of 4.74 points, with 96.8% sensitivity and 99.5%specificity for the prediction of mortality.Conclusion T he high SICK score is associated with higherprobability of death. A cut off score of 4. 74 has high sensitivity andspecificity for predicting the probability of death. The SICK scoremay be useful as a triage tool at the patient's initial presentation,particularly in settings with limited resources.